Self-Efficacy pada Hasil Belajar Peserta Didik Materi Bentuk Aljabar Madrasah Tsanawiyah Tanjungpinang - Meisha Nuraisyah; Nur Izzati (Jurnal Pendidikan Matematika RAFA, 2020)
Self-efficacy is one of the factors that affect student learning outcomes. This study was conducted in order to the relationship between self-efficacy with learning outcomes to describe how much the relationship between self-efficacy and learning outcomes, for algebraic form involving twenty-seven 7 grader students of Madrasah Tsanawiyah in Tanjungpinang. To achieve this goal, this study used a correlation technique with a quantitative approach. The analysis was conducted in the form of self-efficacy questionnaire analysis and learning formative tests. Data analysis was performed using Pearson Product Moment correlation techniques with a significance level of 0.05. After doing the analysis phase, this study obtained a correlation coefficient (r = 0.906), the figure can be said to be very strong based on correlation coefficient interpretation as the researcher's reference. In other words, there was a positive and significant relationship between self-efficacy and learning outcomes, for algebraic form involving twenty-five 7 grader students of Madrasah Tsanawiyah in Tanjungpinang.